(untitled) (Fiep Bulletin - online, 2014)
Introduction:The Piracema Project -Swimming for Carriers of Special Needs, is developed in partnership with the University of Santa Cruz do Sul - UNISC and Association of Parents and Friends of the people with special needs (APAE). It is an extension project of the university and acts since 1984, at the Pedagogical Pool of UNISC. To begin the project, individuals are subjected to a battery of tests, and after the aquatic intervention of 6 months, are conducted the post-tests. Objective: provide people with special needs an opportunity to develop experience in the water and with water as a means of promoting its development as a human being, contributing to the process of inclusion. Methodology: the study subjects were, 16 people with special needs, aged between 09 and 40 years. This battery of tests, they realized medicine ball throwing, horizontal jump and flexibility. Results: In the medicine ball test 93.75% increased their indexes, 6,25% decreases, all participants evaluated realized the test. On the test of horizontal jump, we note that in relation to the pre - and post-test their indices increased 75%, 6,25% decreased its rates and 18.75% of the evaluated participants failed to perform the test. In the test of flexibility, 56,25% increased its index, 31.25% decreased their indices, 6,25% maintained the same index of the pre-testing and 6,25% not performed the test. Conclusion: With regard to the study about the somatomotor profile of the Piracema Project participants we noted that through an intervention of fun-aquatic activities for a period of 6 months, we had a significant improvement in the participants evaluated. So, considering their problems and pathologies, the indexes are presented below the deemed Healthy Physical Fitness Zone (ZSApF)-by-PROESP-US.